The interconnection between musicality and classical ballet technique in Adagio and Allegro - 5th year I Escola Artística de Dança do Conservatório Nacional - Chapman, Caroline (2022)
Internship report submitted to the Escola Superior de dança in candidacy for the degree in Master of Dance Education